Uwagi o metodzie kojarzenia koncentracji naprężeń W. Moszyńkiego - PINDERA, Jerzy Tadeusz (Engineering Transactions, 1956)
Some remarks on the method of evaluation of stress concentrations in combined notches proposed by W. Moszynski In this paper the results of experimental verification of the method of evaluation of stress concentrations in combined notches, proposed by W. Moszyński are presented. Several types of notches were investigated by the photoelastic method. Although the number of the investigated notch types is too small to permit conclusions of a more general character, the results obtained confirm the supposition of the inventor of the method that it can be used in engineering practice, at least in some particular cases, for a preliminary determination of shape coefficients of combined notches. There exists however the necessity of further investigation of the more important notch combinations.